(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Background: Pneumonia is very common disease. The aim of the study was to find out the determinants of community acquired pneumonia (CAP) among children and association of demographics. Subjects and methods: This cross sectional study was conducted from September 2017 to January 2018 Pediatrics department of Sir Ganga Ram Hospital. Hundred pneumonic children under the age of five years were screened by non-probability convenient sampling. Pre-tested questionnaires were used for the collection of data. Results: Out of 100 pneumonic children, the percentage of males was 66%, 51% of families were from low socioeconomic status and 59% of pneumonic children had incomplete vaccination course. 63% of mothers were not having enough knowledge regarding pneumonia, 42% of children had poor sanitary habits and 55% children were having exposure to tobacco. Conclusion: Study concluded that incomplete vaccination, less practice of exclusive breast feeding, excessive tobacco exposure, lack of enough knowledge regarding pneumonia, low socioeconomic status were found to be the contributing factors in CAP.